ame-miR-5119-Eth axis modulates larval-pupal transition of western honeybee worker - Dong, Shunan; Li, Kunze; Zang, He; Song, Yuxuan; Kang, Jing; Chen, Ying; Du, Liting; Wang, Ning; Chen, Dafu; Luo, Qingming; Yan, Tizhen; Guo, Rui; et al. (Frontiers in Physiology, 2024)
The miRNA plays a key role in the regulation of hormone signaling in insects. The pathways by which miRNAs affect hormone levels are unclear in the honeybee (Apis mellifera), an indispensable pollinator in nature. In this study, ame-miR-5119 was overexpressed and knocked down in larvae by feeding mimics and inhibitors, respectively, and we determined that ame-miR-5119 regulates hormone signaling through the target gene ecdysis triggering hormone (Eth), which affects the larval-pupal transition of workers. The results showed that ame-miR-5119 with a length of 19 nt targets six genes related to the hormone pathway. We focused on Eth and found that ame-miR-5119 and Eth exhibited reverse expression patterns during the transition from larval to pupal stages in workers. Dual luciferase assay confirmed the negative regulatory between ame-miR-5119 and Eth. Overexpression of ame-miR-5119 decreased the mRNA level of Eth, and the Eth receptor (Ethr) expression was not significantly affected, but the expression levels of juvenile hormone (JH) pathway related genes juvenile hormone acid methyltransferase (Jhamt) and Krüppel homolog 1 (Kr-h1) were significantly reduced. In contrast, knockdown of ame-miR-5119 increased the mRNA level of Eth, and the expression of Ethr, Jhamt and Kr-h1 was significantly upregulated. ame-miR-5119 did not affect larval body weight. The number of larvae overexpressing ame-miR-5119 survived in the prepupal stage was lower than that in the control group, and the number of pupations reduced at 11-day-old. The number of larvae that knocked down ame-miR-5119 survived in the prepupal stage was significantly higher than that in the control group, and the number of pupations increased at 11-day-old. These results indicated that ame-miR-5119 negatively regulates the expression of Eth, indirectly inhibits the expression of Ethr, Jhamt, and Kr-h1, and affects the JH biosynthesis, thereby preventing the metamorphic transition from larva to pupa in worker bees. These findings provide evidence that the miRNA regulation of hormone levels in honey bees.